Análises de genomas de Bacillus thuringiensis subsp. israelensis isolados em Tocantins com toxicidade para mosquitos de interesse em saúde pública - Alves, Giselly Batista (Universidade Federal do Tocantins, 2017)
Bacillus thuringiensis subsp. israelensis is a gram-positive bacterium widely used to control insects of the order Diptera, such as Aedes aegypti (Diptera: Culicidae) and Culex quinquefasciatus (Diptera: Culicidae). The sequencing of complete genomes of B. thuringiensis strains has allowed the identification and characterization of insecticidal proteins, as well as the comparative genomic studies, allowing the identification of functional and phylogenetic differences. In this context, the present study aimed to perform genomic analysis of four isolates of B. thuringiensis subsp. israelensis having different toxicities for larvae of A. aegypti and C. quinquefasciatus larvae. Sequencing of genomes of the isolates T0124, T0131, T0137 and T0139 was performed from the MiSeq-Ilumina platform, and assembly and annotation were done using tools from the Geneious bioinformatics program. The analyzes resulted in chromosomes with approximate sizes of 5,414 Kb, G + C content of 35.2% and 5,358 coding regions. Regarding extrachromosomal content, three smaller plasmids of 5.4, 6.8 and 7.6 Kb, and three larger plasmids of 127, 235 and 359 Kb were assembled for all the isolates, and these were enumerated from 1 to 6. The annotation revealed that only the plasmids of number 4, corresponding to pBtoxis, possess insecticidal proteins, being Cry4Aa, Cry4Ba, Cry11Aa, Cry10Aa, Cyt1Aa, Cyt2Ba and Cyt1Ca. Comparative analysis between the genomes demonstrates that chromosomes T0124, T0131, T0137 and T0139 have collinear sequences and 99% identity, and their respective plasmids 1, 2, 3, 4, 5 and 6 share all of their coding regions, including those related to δ-endotoxins. Comparison of enterotoxin, metalloprotease and phospholipase sequences shows that these are conserved among the genomes. In the phylogenetic analysis, chromosomes T0124, T0131, T0137 and T0139 were grouped together with the genomes of the isolates AM65-52 and HD-789 available in GenBank, suggesting a close genetic relation between strains of B. thuringiensis subsp. israelensis. The isolates T0124, T0131, T0137 and T0139 present different lethal concentrations to larvae of A. aegypti and C. quinquefasciatus, and the addition of proteomic data to the genomic data obtained here may help to understand these differences in toxicity. However, the comparative analyzes between the genomes of isolates T0124, T0131, T0137 and T0139 show a high degree of genetic conservation at the nucleotide level of B. thuringiensis subsp. israelensis.